The effect of snakehead fish (Channa striata) snacks on nutrition outcomes of adolescence female at risk of chronic energy deficiency - Mustafa, Annasari; Soelistyorini, Dwie; Pudjirahaju, Astutik; Kristianto, Yohanes; Wardhani, Selsabilla Aulia; Safitri, Puput Dewi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2025)
Background: Chronic energy deficiency (CED) is still prevalent in Indonesia, affecting 36.3% adolescent females. The high protein content in snakehead fish presents a promising solution to address the problem.Objectives: This study was aimed to determine the effect of snacks developed using snakehead fish on nutrition outcomes of adolescence females.Methods: The study was conducted using a quasi-experimental quantitative design with a one-group pre-test and post-test approach. Three types of snakehead fish-based snacks —Ekado, Soymay, and Nuggets —were developed and administered to female senior high school students at risk of CED. The snacks were provided twice a week for a period of two months. Nutrient intakes, mid-upper arm circumference (MUAC), and body mass index (BMI) were measured at the commencement and conclusion of the study. The results were then compared to examine the snacks effects.Results: Before the study, most subjects were deficient in energy and macro nutrients. The subjects well accepted the developed snacks. The administration of the snacks significantly increased (p < 0.05) the intake of energy from 61.06 to 73.01 percent of their recommended daily allowance. The treatment also significantly (p < 0.05) reduces the number of subjects at risk of CED from 93.94% to 60.61% and those who are very thin from 42.42% to 24.24%.Conclusions: The administration of snakehead fish-based snacks appears to be a successful strategy in promoting the consumption of macronutrients, MUAC, and BMI of female adolescents at risk of CED.